How does climate exacerbate root causes of conflict? Mapping the science around climate security - Carneiro, Bia; Resce, Giuliano; Läderach, Peter R.D.; Pacillo, Grazia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This factsheet gives answers on how global climate research addresses the dynamics between climate, socio-economic factors, and conflict, and how the countries in focus for the Climate Security Observatory are represented in this literature. The analysis has found that while the literature is cognisant of the mechanisms by which climate exacerbates the risk for conflicts, there is still space for research that aims to disentangle the complexity of the climate security nexus.